Extracellular vesicles: molecular messengers and new therapeutic targets in acute myocardial infarction - Wu, Hao; Xue, Jinyi; Liu, Qiuyu; Wan, Zhenxun; Liang, Lingling; Sun, Shihan; Liu, Ping; Chen, Mingtai; Liu, Mengnan (Frontiers in Immunology, 2025)
Extracellular vesicles (EVs) are nanoscale particles secreted by cells, encapsulating a variety of biomolecules, and have emerged as significant players in the pathophysiology of acute myocardial infarction (AMI). These vesicles exhibit both detrimental and therapeutic effects. On one hand, EVs contribute to AMI progression by promoting apoptosis, exacerbating inflammatory responses, and impairing angiogenesis. On the other hand, they facilitate cardiac repair by enhancing neovascularization, mitigating programmed cell death, and inhibiting fibrosis. This review provides a comprehensive overview of EV biogenesis, release mechanisms, and their dual regulatory roles in AMI, emphasizing the complex interplay of EVs in myocardial injury. Additionally, it explores the potential of EVs as diagnostic biomarkers and therapeutic delivery vehicles, highlighting their importance in advancing diagnostic and therapeutic strategies. By elucidating the multifaceted roles of EVs, this review aims to establish a foundation for their clinical translation, improve their applicability in precision medicine, and explore the promising potential in cardiovascular disease treatment.